PENGARUH LITERASI ZAKAT TERHADAP MINAT MUZAKKI MEMBAYAR ZAKAT PADA LAZNAS AL-IRSYAD PURWOKERTO DENGAN RELIGIUSITAS SEBAGAI VARIABEL INTERVENING - Hanza Mutiara Hakki; Sulasih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of modern business is marked by intense competition, rapid market changes, and the The development of philanthropy in Indonesia is experiencing progress, marked by the emergence of various types of Zakat Institutions, one of which is LAZ Al-Irsyad. Zakat institutions are bodies that manage sources of funds received from muzakki and are one of the institutions whose role is to receive zakat or distribute zakat funds to people in need (mustahik). In this research, researchers are interested in researching muzakki's interest in paying zakat at LAZNAS Al-Irsyad Purwokerto because people's interest in paying zakat at zakat institutions is still less than optimal. This researcher aims to test the influence of zakat literacy on muzakki's interest in paying zakat at LAZNAS Al-Irsyad Purwokerto with religiosity as an intervening variable. This study uses a quantitative approach. Primary data from this research was obtained using a non-probability sampling technique with research sampling using purposive sampling. The population of this research is muzakki LAZNAS Al-Irsyad Purwokerto with a total sample of 202 respondents. This research uses the Structural Equation Model-Partial Least Square (SEMPLS) method by testing the hypothesis using SmartPLS software. The results of this research show that zakat literacy and religiosity have a significant influence on muzakki interest in LAZNAS Al-Irsyad Purwokerto, as well as zakat literacy has a significant influence on religiosity. Meanwhile, the mediation effect based on test results shows that religiosity is able to mediate zakat literacy on muzakki's interest in paying zakat at LAZNAS Al- Irsyad Purwokerto.